2009
DOI: 10.1097/aog.0b013e31818db36f
|View full text |Cite
|
Sign up to set email alerts
|

Active Compared With Expectant Delivery Management in Women With Gestational Diabetes

Abstract: Active rather than expectant management of labor at term for women with GDM may reduce rates of macrosomia and related complications. Further RCTs and observational studies with a broader range of outcomes are needed for sufficient evidence to inform clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 10 publications
0
42
0
3
Order By: Relevance
“…A number of studies advocating superiority of active management of peripartum period in women with GDM suggested 38 th week as the most favourable time to perform induction and preinduction in terms of neonatal complications [18][19][20][21]. Due to existing data that elective induction of labour in patients with mild GDM does not increase the risk of caesarean section until the end of the 40 th gestational week, the most common recommendation is to perform induction on qualified patients between 38 th and 40 th gestational week [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies advocating superiority of active management of peripartum period in women with GDM suggested 38 th week as the most favourable time to perform induction and preinduction in terms of neonatal complications [18][19][20][21]. Due to existing data that elective induction of labour in patients with mild GDM does not increase the risk of caesarean section until the end of the 40 th gestational week, the most common recommendation is to perform induction on qualified patients between 38 th and 40 th gestational week [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that elective induction can significantly reduce the rate of LGA and shoulder dystocia, but due to immature cervical ripening of early induction, the failure rate increased. The elective induction at less than 38 weeks has a higher rate of vaginal delivery failure, which results with transit to cesarean section anyways [14]. The results of our study show that there is no difference in the rate of cesarean section, the rate of difficult birth, the incidence of macrosomia or the incidence of neonatal hypoglycemia whether delivered before or after 40 weeks.…”
Section: Discussionmentioning
confidence: 44%
“…In their comparison however the authors did not take into consideration the pregnancy outcomes nor the neonatal outcomes. Witkop et al [14] have reviewed a few studies and found that in case of GDM pregnancy with good glycemic control, the incidence of macrosomia and associated complications can be reduced if management is active (induction at term) rather than expectant. In 2015 NICE brought to the attention that there was no convincing evidence that GDM pregnancy with appropriately managed glycemia has still an increased risk of a stillbirth but there was sufficient evidence to recommend induction of labor prior to 40 weeks of gestation to reduce the risk of shoulder dystocia [15].…”
Section: Discussionmentioning
confidence: 99%
“…Кесарево сечение в родах при крупном плоде прово-дится в среднем в 2 раза чаще, чем у рожениц со средней массой плода [10,13]. В проведенном исследовании число случаев кесарева сечения при массе плода 4000 г и более составило 30,3%, при родах нормотрофичным плодом -17,5%.…”
Section: Discussionunclassified